2010
DOI: 10.1038/cdd.2009.210
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of diacylglycerol kinase θ mediates adenosine-dependent hepatocyte preconditioning

Abstract: In liver ischemic preconditioning (IP), stimulation of adenosine A2a receptors (A2aR) prevents ischemia/reperfusion injury by promoting diacylglycerol-mediated activation of protein kinase C (PKC). By concerting diacylglycerol to phosphatidic acid, diacylglycerol kinases (DGKs) act as terminator of diacylglycerol signalling. This study investigates the role of DGK in the development of hepatocyte IP. DGK activity and cell viability were evaluated in isolated rat hepatocytes preconditioned by 10 min hypoxia fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
(61 reference statements)
3
23
0
Order By: Relevance
“…To begin this analysis, we first took advantage of the DGK inhibitor R59949. Before describing our results, it is important to mention that the DGK family of enzymes is composed of at least 10 different isoforms, and currently available inhibitors of DGK (R59949 and its weaker analog R59902) preferentially inhibit only the ␣, ␤, ␥, and isoforms of DGK (34,35). Consistent with these points, we found that R59949 (100 M) induces a partial, but significant, inhibition of basal DGK activity (Fig.…”
Section: R59949 Does Not Inhibit the Mechanically Induced Increase Insupporting
confidence: 76%
“…To begin this analysis, we first took advantage of the DGK inhibitor R59949. Before describing our results, it is important to mention that the DGK family of enzymes is composed of at least 10 different isoforms, and currently available inhibitors of DGK (R59949 and its weaker analog R59902) preferentially inhibit only the ␣, ␤, ␥, and isoforms of DGK (34,35). Consistent with these points, we found that R59949 (100 M) induces a partial, but significant, inhibition of basal DGK activity (Fig.…”
Section: R59949 Does Not Inhibit the Mechanically Induced Increase Insupporting
confidence: 76%
“…However, it is now clear that the accumulation of cellular diacylglycerol also depends on the rate of its metabolism to phosphatidic acid by diacylglycerol kinases (DGKs) [36] . In this regard, we recently observed that following IP or A2aR activation, the onset of hepatocyte tolerance to hypoxia was associated with a decrease in DGK activity [37] . Moreover, stimulation of A2aR specifically inhibited DGK isoform θ by activating RhoA-GTPase [37] .…”
Section: Negative Regulators Of Liver Preconditioningmentioning
confidence: 98%
“…Diacylglycerol kinase theta (DGKθ) and the phosphatase tensin-homologues-deleted from chromosome 10 (PTEN) which metabolize diacyglycerol and phosphatidylinositol, respectively, are inhibited during preconditioning to sustain activation of the diacylglycerol (DAG)-dependent PKC δ and ε and the PI3K-dependent signals. See text and Refs [21,25,27,28,32,35,37,43] represents an important pathway in the development of liver IP. Interestingly, PKB/AKT activation in connection with the development of tolerance to I/R was evident in rat hepatocytes and mouse livers [32,34] undergoing IP, as well as in preconditioned human liver grafts immediately after transplantation [35] .…”
Section: Signalling Pathways Involved In Adenosine and Atpinduced Hepmentioning
confidence: 99%
“…The PKC signaling pathway is implicated in a wide range of biological activities and specifically mediates the proliferation and differentiation of a variety of cells. Studies have found that PKC is involved in the preconditioning protection of hepatic ischemia (18). The proliferation and apoptosis of normal cells and hepatic tumor cells closely correlate with PKC (19)(20)(21)(22).…”
Section: Activation Of the δ-Opioid Receptor Inhibits Serum Deprivatimentioning
confidence: 99%